(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
Learning that is carried out online is no exception at MAN 2 Sukabumi City and is a new thing that is also a challenge for every school. These challenges then have an impact on the process and learning outcomes carried out by teachers and students. The learning problem that is seen and becomes a concern during the online history learning process, especially in class X IPS 4 MAN 2 Sukabumi City is the low creativity of students which is included in 21st century skills. There are several indicators of creativity that are low and lacking in students. The current conditions with the implementation of online learning, although recently limited face-to-face meetings have begun, make it necessary to use an online platform to support the learning process and conduct research during this pandemic. Based on these problems, the formulation of the problems taken in this research is how to increase students’ creativity in learning history through the application of flipchart projects with the help of the Whast App application. The method used in this research is a classroom action research (CAR) method using a design developed by Ebbut. Based on the research results, the application of flipchart projects can be a solution to increase students’ creativity in learning history